Effects of PM2.5 exposure on reproductive system and its mechanisms. (February 2021) - Wang, Lingjuan; Luo, Dan; Liu, Xiaolong; Zhu, Jianqiang; Wang, Fengli; Li, Bin; Li, Liming
Abstract: With the development of human society, haze has become an important form of air pollution. Haze is a mixture of fog and haze, and the main component of haze is fine particulate matter (PM2.5 ), which is the most important indicator of composite air pollution. Epidemiological studies proved that PM2.5 can break through the respiratory mucosal barrier and enter the human body, causing pathological effects on multiple systems of the body. In the past, people put more attention to PM2.5 in the respiratory system, cardiovascular system, nervous system, etc, and relatively paid less attention to the reproductive system. Recent studies have shown that PM2.5 will accumulate in the reproductive organs through blood-testis barrier, placental barrier, epithelial barrier and other barriers protecting reproductive tissues. In addition, PM2.5 can disrupt hormone levels, ultimately affecting fertility. Prior studies have shown that oxidative stress, inflammation, apoptosis, and the breakdown of barrier structures are now considered to contribute to reproductive toxicity and may cause damage at the molecular and genetic levels. However, the exact mechanism remains to be elucidated. Our review aims to provide an understanding of the pathological effects of PM2.5 on reproductive system and the existing injury mechanism. Highlights: PM2.5  accumulated in the reproductive organs through BTB and placental barrier, ultimately causing male infertility. PM 2.5  disrupted hormone levels and decreased ovarian reserve. PM2.5  lead adverse perinatal outcome including abortion, PTB, LBW, PROM. Existing toxic mechanisms of PM2.5 are oxidative stress, inflammation, cytotoxicity and barrier structure disturbance.